2003
DOI: 10.1111/j.1365-2494.2003.00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of seasonal dry‐matter yield and quality of grass swards with imaging spectroscopy

Abstract: The potential of imaging spectroscopy for the assessment of seasonal dry-matter (DM) yield and sward quality was studied. Relationships between spatial heterogeneity of tiller density, light interception, ground cover and seasonal DM yield were developed. Sward heterogeneity was quantified by the spatial standard deviation of ground cover and of logarithmically transformed ground cover, and patterns in ground cover transects were quantified by wavelet entropy. An experiment was conducted with eight control (C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…, 2002). In addition to species productivity, the measurements made of nutritive value have a determinant role in the efficiency of pasture utilization, supplying herbivores with the necessary nutrients for maintenance and production (Schut and Ketelaars, 2003). According to their yields of digestible DM and CP values (Figure 3), grasses may be classified into: high (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…, 2002). In addition to species productivity, the measurements made of nutritive value have a determinant role in the efficiency of pasture utilization, supplying herbivores with the necessary nutrients for maintenance and production (Schut and Ketelaars, 2003). According to their yields of digestible DM and CP values (Figure 3), grasses may be classified into: high (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Ground cover and reflection intensity measured by the system is indicative of canopy geometry. Schut and Ketelaars (2003a,b,c) showed that, with this system, the mass and growth of herbage, light interception, sward heterogeneity, N deficiency and drought stress can be studied because of the non‐destructive nature of reflection measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Frequent information on the status of legume–grass swards could help to direct fertilizer applications and to predict the N supply of the soil for the subsequent crop. An indirect assessment of the sward biomass (BM) by field spectroscopy (Biewer et al, 2008, 2009) or imaging spectroscopy (Schut and Ketelaars, 2003a, b; Schut et al, 2006) was shown to produce reliable data but could not determine the legume dry matter (DM) contribution. Based on grayscale images a digital image analysis (DIA) procedure was proposed by Himstedt et al (2009) that allows the estimation of legume DM contribution with an acceptable accuracy for swards with more than 300 kg DM ha −1 .…”
mentioning
confidence: 99%